Redefining Competitiveness: The Role of Lean Production and Eco-Design in the Indonesian FMCG Industry - Rachmawati, Christina; Mahmudy, Wayan Firdaus; Khusaini, Moh.; Kurniawan, Andi (Jurnal Pembangunan dan Alam Lestari, 2025)
The Indonesian FMCG market is booming due to increased consumer spending power. However, this expansion brings challenges, including fierce competition and the potential for escalating production costs. FMCG companies must prioritize innovation to improve operational efficiency and environmental sustainability to stay competitive and profitable. This research explores the strategies employed by a leading Indonesian FMCG company to attain a competitive edge in sustainability by integrating eco-design and lean production principles. The concept of Eco-Design, which emphasizes minimizing environmental impact over the product's lifecycle, is integrated with Lean Production's emphasis on waste reduction and process efficiency. This company is redefining competitiveness by merging these two strategies. It's not just about economic success; it's about achieving that success in a way that prioritizes environmental stewardship and minimizes ecological impact. This holistic strategy seeks to harmonize financial and environmental objectives, creating a mutually reinforcing cycle that fosters a more sustainable and responsible approach to competitive advantage. This study used statistical analysis to confirm that Lean Production and Eco-Design strongly contribute to sustainable manufacturing in the FMCG sector. The findings highlight how combining these two approaches can boost efficiency and sustainability, offering a powerful roadmap for companies in Indonesia and beyond to achieve lasting success in a rapidly changing market. Keywords: eco-design, FMCG market, lean production, prioritize innovation